Dynamic coercivity of Mo-doped FINEMETs - Srimoy, Chakraborty (2011)
The structure and the dc magnetic behavior of FINEMET-type alloys doped with molybdenum have been recently reported. Most commercial applications of these materials are, however, not at dc but at high magnetizing frequencies. Therefore, we report a study of the frequency dependence of coercivity, Hc(f), in amorphous and nanocrystalline ribbons of composition Fe73.5Si13.5Nb3−xMoxB9Cu1 (x=0, 1.5 and 3) in the frequency range from 0.5 to 1.3 kHz. The nature of Hc(f) measurements revealed the influence of eddy currents in the magnetization of samples. The frequency dependence of coercivity did not vary with the molybdenum content in the amorphous samples. All the alloys exhibited a systematic improvement in the coercivity after nanocrystallization and it was found that this improvement was better as more Nb was replaced by Mo.